R2R3-MYB Transcription Factors Regulate Anthocyanin Biosynthesis in Grapevine Vegetative Tissues - Xie, Sha; Lei, Yujuan; Chen, Huawei; Li, Junnan; Chen, Huangzhao; Zhang, Zhenwen (Frontiers in Plant Science, 2020)
Anthocyanins with important physiological functions mainly accumulate in grape berry, but teinturier grape cultivars can accumulate anthocyanins in both reproductive and vegetative tissues. The molecular regulatory mechanisms of anthocyanin biosynthesis in grapevine reproductive and vegetative tissues are different. Therefore, teinturier grapevine cultivar provides opportunities to investigate transcriptional regulation of vegetative anthocyanins, and to compare with mechanisms that regulate grape berry anthocyanins. Yan73 is a teinturier Vitis vinifera variety with vegetative tissues able to accumulate anthocyanins, but the anthocyanin pattern and the molecular mechanism regulating anthocyanin biosynthesis in these tissues remain uncharacterized. We analyzed the anthocyanin metabolic and transcriptome profiles of the vegetative tissues of Yan73 and its male parent with HPLC-ESI-MS/MS and RNA-sequencing technologies. Yan73 vegetative tissues had relatively high 3′-OH, acylated, and methoxylated anthocyanins. Furthermore, peonidin-3-O-(trans-6-coumaryl)-glucoside is the most abundant anthocyanin in Yan73 grapevine vegetative tissues. A total of 30,17 and 10 anthocyanin biosynthesis genes showed up-regulated expression in Yan73 leaf, stem and tendril, respectively, indicating anthocyanin biosynthesis in Yan73 vegetative tissues is regulated by transcription factors. The up-regulated expression of VvMYBA1 on chromosome 2 and VvMYBA5, VvMYBA6, and VvMYBA7 on chromosome 14 are responsible for the anthocyanin patterns of Yan73 vegetative tissues. The expression of a set of R2R3-MYB C2 repressor genes is activated and may negatively regulate anthocyanin biosynthesis in Yan73 vegetative tissues. These findings enhance our understanding of anthocyanin biosynthesis in grapevine.